Assessing risk and uncertainty in fisheries rebuilding plans - Urs Steiner Brandt; Niels Vestergaard (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2011)
This paper deals with risk and uncertainties that are an inherent part of designing and implementing fisheries rebuilding plans. Such risk and uncertainties stem from a variety of sources, biological, economic and/or political factors, and are influenced by external factors like changing environmental conditions. The aim of this paper is to characterize such risks and uncertainties and to assess the importance of it in relation to the performance of fisheries rebuilding plans, to give some examples where uncertainties have negatively affected the ability of rebuilding plans to reach their intended targets and to give some guidelines how to deal with risk and uncertainties.
Keywords: 330; Fischschutz; Fischereiressourcen; Fischereipolitik; Entscheidungstheorie; Nordsee; Pazifischer Ozean